Volymsrapportering vid terrängtransport av virke - Collin-Karlsson, Robin (2011)
This report is a B.Sc. Forestry thesis work at the school for Forest Management, SLU. The work was an assignment from the forest owners’ association Mellanskog. The aim of the work where to investigate the economical result of removing undergrowth trees before first thinning, and a follow-up of the contractors and their compliance with Mellanskog standards. This thesis work was divided in three parts: The first was to find a relation between the net volume from the first thinning and the cost of cleaning undergrowth trees. Secondly there was a follow-up in the field, to investigate whether the contractors have done the undergrowth cleaning according to Mellanskog’s directives. The last part of the assignment was an inquiry examination to both thinning machine contractors and cleaning contractors, including interviews with some of them. One hypothesis, which we shared with our assigner (Mellanskog), was that all contractors didn`t follow the directives. According to the directive all obstructive undergrowth up to 8 cm diameter in breast height (1,3 meters above the ground) should be removed. Trees with a breast height diameter <8 are common in first thinning stands after cleaning, which is unprofitable for all links of the forest supply chain. Results from the field investigation, shows that 17 % of all remaining trees after cleaning are less than 8 cm breast height diameter. The history of forest management plays a crucial role for the result of undergrowth cleaning. If cleaning has been made once or twice earlier in the stand, the contractor`s job is easier since selection of main stems is already done. Otherwise the contractors made a god job according Mellanskog’s directive. The investigations show that there is a connection between average stem volume (solid under bark) and the cost of cleaning. If the average stem is small the cost will be high and vice versa. Result from the inquiry shows that the contractors understand well how the undergrowth cleaning should be done in theory, in practice, result shows that the contractors does not comply with the directive, i.e. to remove all obstructive undergrowth up to 8 cm diameter in breast height (according to the machine contractors). One positive observation is that the machine contractors have also experienced an obvious improvement of the undergrowth cleaning in the last years.